(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2024)
Fire-induced rock exfoliation is a rapid mechanical weathering process characterized by an uneven heating and thermal expansion stress that causes the detachment of rock peels, flakes or spalls. We examined 18 granitoid erratic blocks on a gradient of fire severity in a burned inselberg near El Bolsón, during March 2023. Among them, 13 blocks showed fire spalling, producing 0.1 to 6 kg/m2 of sediment on rock surfaces with an average of 1.72 kg/m2. The incidence of fire spalling showed a more pronounced occurrence within areas of higher severity above dNBR 800. This study is the first mention of fire-induced weathering in the Patagonian Andes, which underlines the need to investigate the intricate relationship between forest fires and the denudation of vegetated outcrops in the region.